Numerical Studies of Premixed and Diffusion Meso/Micro-Scale Flames. (August 2017) - Cova, A.; Resende, P.R.; Cuoci, A.; Ayoobi, M.; Afonso, A.M.; Pinho, C.T.
Abstract: This work reports a numerical investigation of premixed and diffusion meso/micro-scale flames, with homogeneous reactions, for two different cases involving CH4 /air premixed dynamics flames and co-flow diffusion flame with H2 /N2 mixture. In the first case, the numerical predictions are able to capture the flame characteristics behaviour for different fuel equivalent ratio and geometries, showing the accuracy of the reactions model, which uses a very detailed kinetics. In the second case, the analysis concerns the effect of a porous bluff body in pollutants emissions, especially the NOx formation, at meso scale, considering different porous temperatures and geometrical configurations.